The impact of low oil prices on investments - Morse, E; Haas, P; Terzian, G; Aissaoui, A (Oxford Institute for Energy Studies, 2009)
Edward L. Morse believes the supply shortfall may fall less short than assumed; Pedro Haas and Greg Terzian look at petroleum industry E&P; capital spending perspectives; Ali Aissaoui assesses the shrinking MENA energy investment outlook.